Computational Liquid Dynamic Simulation Mixing Time from Side Inlet Mixer Tank - Nadia Mumtazah; Ainurazis Ramadhana Putraninghadi; Ni'am Nisbatul (Universitas Muhammadiyah Sidoarjo, 2021)
This study aims to investigate the mixing time of the side-entry mixer tank and the influence of the propeller's rotational speed on mixing time by the Computational Fluid Dynamic (CFD) method. The tank's model is a flat-bottom cylinder tank whose diameter is 40 cm with a 6 cm propeller contains three blades. The tracer, HCL 37%, was injected on the water's surface while the propeller's rotation speed is varied 100 rpm, 200 rpm, 300 rpm, and 400 rpm. The simulation process is examined using CFD FLUENT 17.1, with a turbulence model is k-ɛ RNG. Its conditions are single-phase then proceeded using species transport. Furthermore, the monitoring point's simulation is identical to the experimental data monitoring probe, which is used to inspect the mass fraction at each point. After all, this simulation contains three processes: pre-processing, solving, and post-processing. as a result, the propeller's higher rotational speed makes the mixing time shorter in the CFD method, which has a good agreement with the experimental method. Moreover, this study also examines the impact of the grid's type and the geometric size for the mixing process in the side-entry mixer tank.